GE_GERICHTE P/26369/2017 vom 13. Mai 2019 - GE Cour de justice (2019)
QUALITÉ POUR RECOURIR ; ACTIONNAIRE ; SOCIÉTÉ ANONYME ; DROIT D'ÊTRE ENTENDU ; ESCROQUERIE ; GESTION DÉLOYALE | CPP.310; CPP.115; Cst.29.al2; CP.146; CP.158